The impact of diversified intelligences on intermediate EFL learners L2 writing skills - Mohammad Awad Al-Dawoody Abdulaal; Amal Zakaria Mahmoud Hal; Nesreen Saud AlAhmadi; Ahmad Abdel Tawwab Sharaf Eldin; Ahmed Ismail Qutb Mohammed; Naglaa Fathy Mohammad Atia Abuslema (Universitas Syiah Kuala, 2025)
The goal of this study was to determine how diversified intelligence (DI) can predict various aspects of L2 writing. To achieve this, 120 intermediate English as a Foreign Language students were selected using the Oxford Quick Placement Test (OQPT). The learners were given Abdulaal, Alenazi et al.s (2022) DI questionnaire. The participants were asked to prepare an argumentative essay in sixty minutes on a given subject. Each writing componenttenor, organization, coherence, vocabulary, grammar, spelling, and pronunciationwas considered when assigning a score to the students writings. The inter-rater reliability, as determined by Pearsons correlation, was 0.87. The data were analyzed using multivariate regression in AMOS (Version 22) to answer the following basic research question: Which types of DIs contributed to various characteristics of L2 writing? The findings demonstrate how diversified intelligence impacted different aspects of learners writing. It was discovered that intrapersonal, musical, and naturalistic intelligence significantly impacted the grammar of EFL students writings; kinesthetic, existential, logical, and naturalistic intelligence had an impact on the punctuation components of L2 writings; verbal, kinesthetic, and naturalist intelligence had influences on students writing organization; visual, interpersonal, logical, and existential intelligence played a significant role in the students cohesion; and finally, logical, and existential intelligence significantly impacted the relevance and sufficiency of the thematic tenor.